Part 1 - 7 Islands Medical Tourism Business Plan 2011-2013 Part 2 - Using Strategic Entrepreneurship To Overcome Lack Of Competitor Analysis And Changing Market Dynamics In Medical Tourism - Shah, Bhartendu (2010)
This paper discusses the importance of effectively practicing opportunity – seeking behaviour and advantage – seeking behaviour for small owner / manager firms in order to succeed in the dynamic business environment of Medical Tourism. It identifies how the combination of certain entrepreneurial characteristics with the strategic management of resources can greatly mitigate the uncertainties of competing in the nascent Medical Tourism business. It makes recommendations for small entrepreneurial firms in general on how to capitalise on their innovative ideas by making a successful new entry. Finally, it raises a research question as to how can small entrepreneurial firms overcome their lack of resources to swiftly establish their new domain and scale up the venture.